2014
DOI: 10.1039/c4ta04339a
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited nickel-sulfide films as competent hydrogen evolution catalysts in neutral water

Abstract: The development of low-cost, efficient, and robust electrocatalysts of the hydrogen evolution reaction (HER) is a crucial step toward the conversion and storage of sustainable and carbon-neutral energy resources, such as solar energy. Not only the HER catalysts need to be composed of inexpensive elements, they are also desirable to be prepared at low energy cost. In this work, we report that nickelsulfide (Ni-S) films prepared by facile potentiodynamic deposition are active HER catalysts in aqueous media. Nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 195 publications
(146 citation statements)
references
References 51 publications
6
140
0
Order By: Relevance
“…This would indicate that under air exposure the doping Ni atoms spontaneously increase their oxidation state to Ni 2+ as found in NiO species, agreeing with the behavior observed for bare Ni nanoclusters. Presence of a nickel sulfide phase cannot be discarded from XPS results as it is well reported that directly bonded S atoms leave the Ni 2p 3/2 peak position unaltered, 28 and the S 2p 3/2 :2p 1/2 doublet overlap commonly reported in nickel sulfides 29 is also found in the bare (MoS 2 ) 300 nanoclusters. However, the upward shift of the Ni 2p 3/2 component to binding energies similar to those of NiO species after air exposure makes the presence of a nickel sulfide phase unlikely.…”
Section: Resultsmentioning
confidence: 99%
“…This would indicate that under air exposure the doping Ni atoms spontaneously increase their oxidation state to Ni 2+ as found in NiO species, agreeing with the behavior observed for bare Ni nanoclusters. Presence of a nickel sulfide phase cannot be discarded from XPS results as it is well reported that directly bonded S atoms leave the Ni 2p 3/2 peak position unaltered, 28 and the S 2p 3/2 :2p 1/2 doublet overlap commonly reported in nickel sulfides 29 is also found in the bare (MoS 2 ) 300 nanoclusters. However, the upward shift of the Ni 2p 3/2 component to binding energies similar to those of NiO species after air exposure makes the presence of a nickel sulfide phase unlikely.…”
Section: Resultsmentioning
confidence: 99%
“…[27,148,149] It is found that the potentiodynamic deposition mode can facilitate the formation of CoS compounds as compared with the conventional chronoamperometric method, which can be attributed to the more efficient formation of Co(II)-TU complexes under the potentiodynamic condition. [142] Despite, it is also possible to achieve well-ordered nanoarrays under chronoamperometric conditions by changing the electrolyte constitutions.…”
Section: Potentiodynamic Deposition Of Well-ordered Transition Metal mentioning
confidence: 99%
“…After demonstrating CO 2 -to-CH 4 conversion by M. barkeri during in situ electrolysis using a platinum HER cathode, we sought to replace the precious metal catalyst with an earth-abundant alternative. Several HER catalysts containing only first-row transition metals have been recently reported (57)(58)(59)(60); among these examples, metal chalcogenides have featured prominently (61)(62)(63)(64)(65)(66)(67). In addition to low overpotential and long-term stability, another requirement for a catalyst in a biomaterials hybrid system is that it must operate in aqueous media within a biologically relevant pH range (pH [5][6][7][8] and be nontoxic to the organism.…”
Section: Electrochemical Reduction Of Carbon Dioxide To Methane With Amentioning
confidence: 99%